Therapeutic potential and mechanisms of stem cells in major depressive disorder: a comprehensive review - Li, Jiaqi; Wang, Yuqian; Zhang, Yucheng; Liu, Mengran; Rong, Xinao; Jiang, Jinlan (Frontiers in Pharmacology, 2024)
Depression is a common affective disorder characterized by persistent low mood, diminished interest or pleasure in normally enjoyable activities, disturbances in sleep patterns, and suicidal ideation.Conventional treatments often yield unsatisfactory results and are associated with several adverse effects. However, emerging literature has highlighted the potential of stem cell (SC) transplantation as a promising avenue for treating depression owing to its favorable anti-inflammatory and neurotrophic properties. This review summarizes the therapeutic effects and underlying mechanisms associated with SC transplantation in depression, offering a conceptual framework for the future application of SCs in the clinical treatment of depression.